Electrocardiographic localization of ventricular arrhythmias successfully ablated from the distal great cardiac vein. (15th July 2020) - Chang, David; Gabriels, James; Vaishnav, Aditi; Kim, Beom S.; Coleman, Kristie; Khan, Mohammad; Maisel, Kyle; Ismail, Haisam; Goldner, Bruce; Willner, Jonathan; Mitra, Raman; John, Roy M.; et al.
Abstract: Background: Idiopathic ventricular arrhythmias (IVAs) from the left ventricular (LV) summit may be successfully ablated from the distal great cardiac vein (dGCV). Using a 12‐lead electrocardiogram (ECG) to localize IVAs that can be ablated from the dGCV is valuable for ablation planning. Objective: To determine if a "w" wave, a notch in the Q wave in lead I, and other ECG features can identify IVAs that can be successfully ablated from the dGCV. Methods: We reviewed outflow tract premature ventricular contraction (PVC) ablations performed at two centers between September 2010 and June 2018. Successful PVC ablations, in which the PVCs were mapped from the right ventricular outflow tract, coronary cusps, commissures, endocardial LV, and the coronary venous system including the dGCV were included. ECG characteristics were compared between patients with successful ablations in the dGCV and non‐dGCV sites. Results: Of the 120 patients (age 56.8 ± 13.8 years, 45% female) that met the inclusion criteria, the dGCV was the successful ablation site in 18 patients (15%). Multivariate analysis with binary logistic regression showed that a "w" in lead I in combination with an early precordial pattern break and a maximum deflection index (MDI) ≥ 0.5 had sensitivity and specificity for a successful ablation in the dGCV of 94.4% and 96.1%, respectively. Conclusion: Combining a "w" wave in lead I with an early precordial pattern break and an MDI ≥ 0.5 is highly sensitive and specific for identifying the dGCV as a successful ablation site for PVCs.